Genetics and selective breeding of variation in wing truncation in a flightless aphid control agent. Issue 7 (17th July 2019) - Lommen, Suzanne T.E.; Koops, Kees G.; Cornelder, Bardo A.; de Jong, Peter W.; Brakefield, Paul M.
Abstract: Augmentative biological control by predaceous ladybird beetles can be improved by using flightless morphs, which have longer residence times on the host plants. The two‐spot ladybird beetle, Adalia bipunctata (L.) (Coleoptera: Coccinellidae), is used for the biological control of aphids in greenhouses and on urban trees. Flightlessness due to truncated wings occurs at very low frequency in some natural populations of A. bipunctata . Pure‐breeding strains of this 'wingless' genotype of A. bipunctata can easily be obtained in the laboratory. Such strains have not been commercialized yet due to concerns about their reduced fitness compared to wild‐type strains, which renders mass production more expensive. Wingless strains exhibit, however, wide intra‐population phenotypic variation in the extent of wing truncation which is related to fitness traits. We here use classical quantitative genetic techniques to study the heritability and genetic architecture of variation in wing truncation in a wingless strain of A. bipunctata . Split‐families reared at one of two temperatures revealed strong family‐by‐temperature interaction: heritability was estimated as 0.64 ± 0.09 at 19 °C and 0.29 ± 0.06 at 29 °C. Artificial selection in opposite directions at 21 °C demonstrated that the degree of wing truncation can be altered within a few generations resulting in wingless phenotypes without any wing tissue (realized h 2  = 0.72), as well as those with minimal truncations (realized h 2  = 0.61) in two replicates. The latter lines produced more than twice as many individuals. This indicates that selective breeding of wing truncation may be exploited to improve mass rearing of flightless strains of A. bipunctata for commercial biological control. Our work illustrates that cryptic variation can also be a source for the selective breeding of natural enemies. Abstract : Wingless strains of Adalia bipunctata (Coleoptera: Coccinellidae) can improve augmentative biological control of aphids, but their reduced fitness hampers commercial mass rearing. We show that the degree of wing truncation, which is related to fitness traits, is highly heritable. A few generations of selective breeding on this cryptic variation yielded strains of wingless A. bipunctata with milder truncations and more offspring. This indicates that selective breeding may be exploited to improve mass rearing of flightless strains for commercial biological control.